Wall charge effects on structural properties of a coarse-grained FENE polyelectrolyte confined in slit nanochannels by Brownian dynamics simulation - Jeon, Jonggu; Chun, Myung-Suk (KOREAN SOC RHEOLOGY, 2007)
A polyelectrolyte chain confined in a slit nanochannel exhibits a structural transition from the one in free space. In this paper, the effect of the long-range electrostatic interactions between the xanthan polyelectrolyte and the slit wall on the confined xanthan conformation is investigated via the Brownian dynamics simulation. A neutral and two negatively charged surfaces of polydimethylsiloxane (PDMS) and glass are combined to make four kinds of slit channels with different charge characteristics: i) neutral-neutral, ii) glass-glass, iii) neutral-PDMS and iv) neutral-glass walls. Their walls are characterized by uniform surface charge densities determined from experimental data of zeta potential. Both the nonmonotonic chain size variation and the loss of long-range bond vector correlation, previously observed under confinement in the PDMS-PDMS slit, are also found in the neutral slit, demonstrating the nonelectrostatic origin of such crossover behaviors. As expected, the effect of wall charges is negligible at sufficiently high medium ionic strength of 100 mM but it becomes significant in the opposite limit of 0.01 mM. In the latter case, the high charge density of glass walls strengthens the effective confinement of a negatively charged polyelectrolyte and produces a xanthan structure comparable to that confined in a much narrower neutral slit. The obtained structural data suggest the possibility of controlling the structure of confined polyelectrolytes by the modification of surface charge characteristics of micro/nanofluidic devices in combination with the adjustment of the medium ionic strength.
Keywords: POLYMER-SOLUTIONS; XANTHAN; CHAIN; STATISTICS; VISCOSITY; MODEL; SHAPE